Intertextual relationship between arts: the poetry Retrato, by Cecília Meireles and painting As velhas, by Goya - Fernandes, Mônica Luiza Socio; Luiz, Laís Maykielen de Carvalho (Revista de Letras, 2015)
This article aims to analyze intertextually the poetry Retrato by Cecília Meireles (2006) and pictorial works by Goya (2012), As velhas, trying to approximate them, especially in their thematic content, the time. For this, we used the precepts of Comparative Literature, the notions of Intertextuality, from Julia Kristeva, linked to bakhtinian dialogism, as well as the connection between literature and the visual arts as well observed by Praz (1982) and Souriau (1983). Considering the various relationships that establishes an art with others, in a methodological perspective comparativist, surveys were made of the similarities between the two works expressed in different languages and different periods.